2023
DOI: 10.21608/mid.2023.174718.1411
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Salmonella activity of Gossypium hirsutum leaf extracted with carbonated drink and its toxicological evaluation in-vivo

Abstract: Background: Although antibiotics are used to treat typhoid fever, there is a need to look for alternative treatment methods because Salmonella typhi (S. typhi) has become aggressively resistant to standard antibiotic treatments. Methods: This experimental study used the carbonated beverage "7UP" as the extraction solvent to examine the anti-Salmonella activity of Gossypium hirsutum leaf extract on Salmonella typhi. Extraction of bioactive components of the plant leaf, in-vitro and in-vivo anti-Salmonella activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Additionally, the histological study showed that the administration of chloramphenicol resulted in severe organ damage. For the liver, kidney, and heart, the average histological damage scores at the maximum dosage were 3.5, 4.0, and 3.6, respectively, on a scale where 4 denotes very serious damage [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the histological study showed that the administration of chloramphenicol resulted in severe organ damage. For the liver, kidney, and heart, the average histological damage scores at the maximum dosage were 3.5, 4.0, and 3.6, respectively, on a scale where 4 denotes very serious damage [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Common side effects of chloramphenicol include nausea, vomiting, and diarrhea, which are usually dose-dependent and treatable [7]. These side effects are relatively common and often resolve on their own or with supportive care.…”
Section: Introductionmentioning
confidence: 99%